Analisa Brand Equity Terhadap Brand Loyalitas Pt. Transjakarta - Wendy Fernando (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine whether there is influence of Brand Awareness to Brand Reputation, to know whether there is influence of Service Quality to Brand Reputation, to know whether influence of Staff Behavior to Brand Reputation, to know whether there is influence of Self Congruence to Brand Reputation, and to know whether there is influence of Brand Identification to Brand Reputation, to know whether there is influence of Brand Association to Brand Reputation, to know whether there is influence of Brand Reputation to Brand Satisfaction, to know whether there is influence of Brand Satisfaction to Brand Trust, to know whether there is influence of Brand Trust to Brand Loyalty, The sample used is 600 respondents who become consumer companies with data analysis techniques that are multiple regression using AMOS program.